The lady of Tarpon Springs - Miller, Judith, 1944- (Bethany House, 2018)
Much to the dismay of her Greek family, Zanna Krykos makes a living as a lawyer in Tarpon Springs, Florida. When her friend Lucy needs legal advice about the business she inherited upon her father's passing, she ends up asking Zanna to run the business instead so she can focus on her medical career. Nico Kalos is a Greek diver who has worked on sponging boats in the Aegean Sea since the age of 14, giving him a vast knowledge of the trade. When he hears of an opportunity to lead a group of spongers to the United States, he seizes it. But his excitement is quickly quelled when he arrives only to discover that a young woman with no experience in the business will be in charge of the new crews. But as Zanna and Nico face even more complications than they could have imagined, they must learn to work together or risk everything they've worked so hard for.